Effect of entrepreneur, firm, and institutional characteristics on small-scale firm performance in Ghana - Bernard Kwamena Cobbina Essel; Faizal Adams; Kwadwo Amankwah (Journal of Global Entrepreneurship Research, 2019)
Small-scale firms are essential contributors to employment generation and growth of many economies. In recognition of their salient role, several policy interventions have been implemented to enhance job creation functions of small-scale firms. This study examined one of these interventions, that is, promotion of small-scale firms in Sunyani municipality of Ghana by analyzing the effect of entrepreneurs, firm, and institutional characteristics on the growth of small-scale firms. A cross-sectional survey was conducted involving 200 small-scale firm operators selected through multi-stage sampling. Both descriptive and inferential analytical tools were used to analyze the data. Descriptive techniques employed included means, frequencies, and cross-tabulations. The inferential analysis included the use of multivariate multiple regression techniques that estimate a single regression model with more than one dependent variable simultaneously. The findings show three types of small-scale enterprises viz. processing (dominated by females), artisans, and service sector (dominated by males) at Sunyani municipality of Ghana. The main findings show that demographic factors (sex of operator, completion of formal education at basic school level or junior high school), institutional variables (bank investment and training services), and firm characteristics (artisan and craft industry type) conjointly and significantly influence small-scale firm performance (number of employees and sales or monthly revenue). Consequent implications for developing economies (such as Ghana) include the need for the introduction of entrepreneurship education at basic level of education in addition to the current practice where entrepreneurship education is mostly limited to tertiary institutions or undergraduate levels, and linking provision of investment services with requisite skills training and backstopping in interventions targeting small-scale firms.
Keywords: 650; Small-scale industries; Enterprise; Entrepreneur; Growth; Performance